Leverage and Liquidity Drive Tax Avoidance in Manufacturing Companies: Leverage dan Likuiditas Mendorong Penghindaran Pajak di Perusahaan Manufaktur - Febriana Wulandari; Herman Ernandi (Academia Open, 2025)
Background: Tax avoidance remains a critical concern in fiscal policy, as taxpayers seek to minimize tax obligations through strategies that often comply with legal frameworks.Specific Background: Among these strategies, transfer pricing, capital intensity, leverage, and liquidity are frequently cited as potential determinants, though empirical findings remain mixed. Knowledge Gap: Prior research has yet to fully explore the moderating role of firm size in the relationship between these variables and tax avoidance.Aim: This study investigates the influence of transfer pricing, leverage, liquidity, and capital intensity on tax avoidance, with firm size as a moderating variable. Results: Findings reveal that leverage and liquidity significantly affect tax avoidance, while transfer pricing and capital intensity show no direct effect. Firm size moderates the effect of transfer pricing, liquidity, and capital intensity on tax avoidance, but not the effect of leverage. Novelty: The integration of firm size as a moderator offers new insights into the conditional impact of financial and operational factors on tax avoidance behavior. Implications: These results contribute to the literature by highlighting firm-specific characteristics in tax planning strategies and can inform regulatory policy to better address aggressive tax practices. Highlights: Examines key financial factors influencing corporate tax avoidance. Identifies firm size as a moderating variable in specific relationships. Offers empirical evidence to guide tax policy and future research. Keywords: Transfer Pricing, Tax Avoidance, Firm Size, Leverage, Capital Intensity